Enterotoxigenicity and Antimicrobial Resistance of Staphylococcus aureus Isolated from Retail Food in China - Wang, Wei; Baloch, Zulqarnain; Jiang, Tao; Zhang, Cunshan; Peng, Zixin; Li, Fengqin; Fanning, Séamus; Ma, Aiguo; Xu, Jin (Frontiers in Microbiology, 2017)
Staphylococcus aureus is one of the most common causes of zoonotic agent in the world, which are attributable to the contamination of food with enterotoxins. In this study, a total of 1,150 S. aureus isolates were cultured from 27,000 retail foods items from 203 cities of 24 provinces in China in 2015 and were test for antimicrobial susceptibility. Additionally, the role of the genes responsible for the staphylococcal enterotoxins (SEA to SEE), methicillin resistance (mecA) and the toxigenic capabilities were also assessed. The results showed that 4.3% retail foods were contaminated with S. aureus, and 7.9% retail foods isolates were mecA positive. Some 97.6% of S. aureus isolates were resistant to at least one antimicrobial compound, and 57.5% of these were multi drug resistant (MDR). Resistance to penicillin (83.7%, 963/1,150), was common, followed by linezolid (67.7%, 778/1,150) and erythromycin (52.1%, 599/1,150). The isolates cultured from raw meats showed high levels of resistant to tetracycline (42.8%), ciprofloxacin (17.4%), and chloramphenicol (12.0%) and expressed a MDR phenotype (62.4%). A total of 29.7% S. aureus isolates harbored the classical SEs genes (sea, seb, sec, and sed). The sea and seb genes were the most frequent SEs genes detected. Of note, 22% of the SEs genes positive S. aureus harbored two or three SEs genes, and 16 isolates were confirmed with the capacity to simultaneously produce two or three enterotoxin types. Moreover, nearly 50% of the MRSA isolates were positive for at least one SE gene in this study. Therefore, it is important to monitor the antimicrobial susceptibility and enterotoxigenicity of MDR S. aureus and MRSA in the food chain and to use these data to develop food safety measures, designed to reduce the contamination and transmission of this bacterium. Keywords: Retail foods; Staphylococcus aureus; enterotoxingenicity; methicillin-resistant Staphylococcus aureus; antimicrobial resistance